Pravovoe regulirovanie truda professionalnykh sportsmenov Rossii - Gallyamova, Yu. B. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The sport in Russia were recognized as a full trade rather recently though already long before it became obvious, that for achievement of high sports results the athlete should give trainings and competitions too many time to have an opportunity simultaneously still somewhere to work. In this connection many known athletes, coaches and scientists repeatedly spoke about necessity of social protection of athletes and distribution of the labor legislation on relations between athletes and the physical culture-sports organizations. The author believes that such relations are expedient for adjusting by norms of civil law as relations between athletes and the physical culture-sports organizations have the specificity rises and will not always be coordinated to general provisions of the labor legislation. Taking into account the given circumstance, and also the introduction into action since February 1, 2002 of the new Labor code, the author offers to return to discussion on this theme in her next publications.